Scratch as an innovative learning media to improve Indonesian language understanding in elementary school students - Wahdian, Agus; Arifah, Siti (Indonesian Journal of Educational Development (IJED), 2025)
Indonesian language learning in elementary schools often faces challenges in increasing student engagement and understanding. Therefore, this study aimed to explore the effectiveness of using Scratch as an Innovative Learning Media to Enhance Indonesian Language Comprehension among Elementary School Students. This study employed a quasi-experimental design with a quantitative approach. The sample consisted of 50 fifth-grade students divided into two groups: an experimental group using Scratch and a control group using conventional learning methods. Data were collected through pre-tests and post-tests to measure students' Indonesian language literacy and were analysed using t-tests. The results showed that the experimental group experienced significant improvement in Indonesian language comprehension compared to the control group, with a post-test significance value of 0.000. These findings indicated that using Scratch as a learning medium could enhance student engagement and understanding of Indonesian. The implications of this study suggested that integrating Scratch-based technology could be implemented as an innovative approach to Indonesian language learning, improving the quality of education and providing an effective alternative for language learning in elementary schools. Further research should expand the sample size and duration to explore the long-term impact of technology use in language learning.